Expanding Opportunities and Building Competencies for Young People : A New Agenda for Secondary Education - World Bank (Washington, DC, 2012)
The report offers policy options to support developing countries and transition economies in adapting their secondary education systems to the demands arising from the successful expansion of primary education and the socio-economic challenges presented by globalization and the knowledge-based economy. The work is the result of an extensive consultative process that involved education specialists worldwide.